Organophosphate pesticide exposure in children in Israel: Dietary associations and implications for risk assessment - Berman, Tamar; Barnett-Itzhaki, Zohar; Göen, Thomas; Hamama, Ziva; Axelrod, Rachel; Keinan-Boker, Lital; Shimony, Tal; Goldsmith, Rebecca (Environmental Research, 2020)
Background: Human biomonitoring (HBM) data is increasingly being compared to risk–based screening values to assess human health risk. However, as screening values have not been established for assessing biomarker concentrations of organophosphate (OP) pesticide metabolites, there are few studies using HBM data on urinary OP concentrations to assess human health risk. The purpose of the current study was to measure OP exposure in a sample of children in Israel; to explore associations between dietary patterns and OP exposure; and to assess risk of OP pesticides using urinary metabolite concentrations. Methods: We recruited 103 children in Israel and collected demographic and dietary data and urinary samples, and measured creatinine and dialkyl phosphate (DAP) concentrations. We compared urinary DAP concentrations to international populations and analysed associations between fruit and vegetable consumption and urinary DAP concentrations. Using urinary DAP concentrations, we calculated estimated daily intakes (EDI) of OP pesticides in each child and compared those to the acceptable daily intake (ADI). Results: Concentrations of several dialkyl phosphate metabolites (dimethylphosphate (DMP) and dimethylthiophosphate (DMTP)) were higher in our study population of Israeli children (geometric mean concentrations of DMP and DMTP were 6.6 μg/L and 7.6 μg/L, respectively) compared to children in the US, Canada, Spain, and Denmark. We found positive correlations between total fruit consumption and creatinine adjusted log transformed urinary DMP, DMTP, diethylthiophopshate (DETP), total dimethyl (DM) and total DAP concentrations (p < 0.05), positive correlations between cucumber consumption and diethylphosphate (DEP), DETP and diethyl (DE) concentrations (p < 0.05), and positive correlations between apple consumption and DETP concentrations (p = 0.02). Based on urinary DAP concentrations, we found that a portion of the children in our study had EDIs above the ADI, ranging from 2.9% to 79.4% of the children, depending on the active OP ingredient. Conclusions: We found that Israeli children in our study are widely exposed to OP pesticides; that levels of dimethyl metabolites were high compared to other international populations; and that fruit consumption was associated with higher urinary DAP levels. Using urinary DAP concentration data, we found that a portion of the children in our study may be exposed to OP pesticides at levels above those considered safe.
CRIS-Team Scopus Importer:2020-01-31
Keywords: Biomonitoring; Dialkyl phosphates; Insecticides; Organophosphate pesticides; Risk assessment